Dysfunction and regulatory interplay of T and B cells in chronic hepatitis B: immunotherapy and emerging antiviral strategies - Yu, Fei; Zhu, Yue; Li, Shenghao; Hao, Liyuan; Li, Na; Ye, Fanghang; Jiang, Zhi; Hu, Xiaoyu (Frontiers in Cellular and Infection Microbiology, 2024)
In the context of chronic hepatitis B virus (HBV) infection, the continuous replication of HBV within host hepatocytes is a characteristic feature. Rather than directly causing hepatocyte destruction, this replication leads to immune dysfunction and establishes a state of T-B immune tolerance. Successful clearance of the HBV virus is dependent on the close collaboration between humoral and cellular immunity. Humoral immunity, mediated by B-cell subpopulations, and cellular immunity, dominated by T-cell subpopulations show varying degrees of dysfunction during chronic hepatitis B (CHB). Notably, not all T- and B-cells produce positive immune responses. This review examine the most recent developments in the mutual regulation of T-B cells during chronic HBV infection. Our focus is on the prevailing immunotherapeutic strategies, such as T cell engineering, HBV-related vaccines, PD-1 inhibitors, and Toll-like receptor agonists. While nucleos(t)ide analogues (NUCs) and interferons have notable limitations, including inadequate viral suppression, drug resistance, and adverse reactions, several HBV entry inhibitors have shown promising clinical efficacy. To overcome the challenges posed by NUCs or monotherapy, the combination of immunotherapy and novel antiviral agents presents a promising avenue for future CHB treatment and potential cure.